Frozen section education in an anatomical pathology residency program. - Ndikumana, Robyn; Kirby, Simon (Canadian Journal of Pathology)
Frozen section consultations are important for pathologists, allowing collaboration with surgeons to examine tissue, formulate a diagnosis, and help direct a surgical procedure. Frozen sections remain challenging for many reasons, including the high stakes nature of the experience, irreversible implications of an error, risk of sampling error, artifacts, limited slide quality, and lack of available special studies, among others. Despite these challenges, not all residency programs incorporate formal teaching of frozen sections in their curriculum, and scant literature exists regarding residency training in frozen sections. Objectives: To determine if a frozen section education pilot project is beneficial to an Anatomical Pathology Residency training program, and to explore gaps in medical education surrounding the topic of frozen section education in an Anatomical Pathology training program. Methods: A pilot study of ten teaching sessions among eight anatomical pathology residents at Memorial University was conducted, where two archived frozen section cases were presented at each session. Participants were given a clinical history and were asked to describe the microscopic findings of the touch preparation, frozen section, and ultimately the permanent section, with emphasis on how they would communicate their findings to the surgeon. Following the final teaching session, participants completed a survey to evaluate the value of the teaching sessions. Results: Our study demonstrated that participants felt that they benefited from these sessions and would like to see an emphasis on frozen sections in residency programs, on a regular basis, and beginning exposure to frozen sections early in residency training.